Analysis of the Effects of CO2, H2S Composition, and Temperature on Steam Towards Corrosion Rate in Geothermal Power Plants - Firdaus, muhammad Rafsya; Hidayati, Noor; Ekayuliana, Arifia (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The corrosion in the steam line pipes at the Geothermal Power Plant is caused by acidic substances present in the steam, especially H2S and CO2, originating from the geothermal reservoir. During operation, this leads to thinning of the pipe walls, affecting the pipe's thickness. The purpose of this research is to calculate the corrosion rate and compare the CO2 and H2S composition in each header using Aspen HYSYS software to determine their influence on the corrosion rate. The research findings indicate that the CO2 and H2S composition in the steam significantly affects the corrosion rate in the steam line pipes. Higher concentrations of CO2 and H2S result in a higher corrosion rate, and the higher the temperature, the corrosion rate will increase.